(untitled) (Medical Forum Monthly, 2024)
Objectives:-To compare the results of distraction-compression and compression-distraction in segmental loss of tibia by Ilizarov extent fixator and to see the functional end results of each procedure. Study Design: Comparative study. Place and Duration of Study: This study was carried out in the Department of Orthopaedic, Nishtar Hospital, Multan from April 2008 to March 2010. Materials and Methods: A total of 30 cases were included in the study. Results:-Gap non-union in tibia is a frequently encountered problem in open tibial injuries. Their treatment have been unsatisfactory until the introduction of distraction histeogenesis by Ilizarov, before the end results were often amputation. Gap non-union of upto 5 cm can be managed by initial compression, later on the LLD is addressed and distraction histeognesis whereas gap of >5 cm are amicably managed by segment transport i.e. distraction and later compression between the transported segment to other end of the fracture. Conclusion: Both methods are excellent if the limitations and principles are followed. Our recommendations are gaps of < 5 cm to be managed and compression-distraction of gaps of >5 cm to be managed with distraction-compression mode of treatment.